Pounding of structures modelled as non-linear impacts of two oscillators. - Chau, K.T (Earthquake engineering & structural dynamics.)
A new formulation is proposed to model pounding between two adjacent structures, with natural periods T1 and T2 and damping ratios 1 and 2 under harmonic earthquake excitation, as non-linear Hertzian impact between two single degree of freedom oscillators. For the case of rigid impacts, a special case of our analytical solution has been given by Davis ('Pounding of buildings modelled by an impact oscillator' Earthquake Engineering and Structural Dynamics for an oscillator pounding on a stationary barrier. Our analytical predictions for rigid impacts agree qualitatively with our numerical simulations for non rigid impacts. When the difference in natural periods between the two oscillators increases, the impact velocity also increases drastically. The impact velocity spectrum is, however, relatively insensitive to the standoff distance. The maximum relative impact velocity of the coupled system can occur at an excitation period Tn which is either between those of the two oscillators or less than both of them, depending on the ratios Ti/T2 and 1 2. Although the pounding force between two oscillators has been primarily modelled by the Hertz contact law, parametric studies show that the maximum relative impact velocity is not very sensitive to changes in the contact parameters.